2017
DOI: 10.3389/fpsyt.2017.00281
|View full text |Cite
|
Sign up to set email alerts
|

Traumatization, Loneliness, and Suicidal Ideation among Former Prisoners of War: A Longitudinally Assessed Sequential Mediation Model

Abstract: Although highly researched among veterans, the underlying mechanisms of suicidal ideation (SI) among former prisoners of war (ex-POWs), especially in the long-term, have rarely been investigated. Furthermore, while posttraumatic stress symptoms (PTSS) and loneliness have been individually associated with veteran SI, and both may be differentially implicated by captivity versus war traumas, the interplay between them has yet to be examined. Filling this gap, the current longitudinal study examined a hypothetica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 91 publications
(113 reference statements)
1
20
0
Order By: Relevance
“…The current study was the first to simultaneously assess the relationship between loneliness and both childhood and adulthood trauma, and our results indicated that traumatic exposure in these different developmental periods were positively associated with feelings of deficiencies in both social network size and intimate connections. Current results add to a growing literature attesting to the importance of trauma history in understanding the characteristic nature of the experience of loneliness [14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 69%
“…The current study was the first to simultaneously assess the relationship between loneliness and both childhood and adulthood trauma, and our results indicated that traumatic exposure in these different developmental periods were positively associated with feelings of deficiencies in both social network size and intimate connections. Current results add to a growing literature attesting to the importance of trauma history in understanding the characteristic nature of the experience of loneliness [14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 69%
“…Of the 20 analyses that explored suicidal ideation 12 results indicated that loneliness was a significant predictor variable. Additionally, Stein et al (2017) reported an indirect pathway from post-traumatic stress syndrome (PTSS) to loneliness at the same timepoint predicting later suicidal ideation. Gallagher et al (2014;T2-T3) reported a significant association while Gallagher et al (2014;T1-T3) did not.…”
Section: Narrative Summary Of Study Findingsmentioning
confidence: 99%
“…Several conditions have already been recognized as major risk factors for suicide ideation and suicide attempts among veterans in the postrecruitment period, including diagnoses of depressive disorders, posttraumatic stress disorder (PTSD), substance use disorders, personal traits (e.g., impulsivity), and environmental variables, such as imitation (O'Connor & Nock, ). Specifically, a considerable body of research suggests that previous trauma in general and war‐related trauma in particular are associated with increased risk of suicidal behaviors among veterans (e.g., Stein, Itzhaky, Levi‐Belz, & Solomon, ). However, although these elements may help detect some veterans engaged in self‐injurious thoughts and behaviors (SITB), a much more thorough examination of the combat‐related stressors and their association with SITB is needed.…”
mentioning
confidence: 99%
“…In the generally stressful atmosphere of combat service (Stein et al., ), with the possibly complex and often ambiguous nature of PMIES scenarios, it can be assumed that veterans with high levels of IU may experience more continued distress and a tendency toward depressive attributes and symptoms that are recognized facilitators of SITB. Some studies have found IU to moderate the link between stressful events and worry (e.g., Zlomke & Jeter, ) but not the link between anxiety sensitivity and panic disorder (Carleton et al., ).…”
mentioning
confidence: 99%